A neurobehavioral account for individual differences in resilience to chronic military stress. Issue 5 (5th September 2014) - Lin, T.; Vaisvaser, S.; Fruchter, E.; Admon, R.; Wald, I.; Pine, D. S.; Bar-Haim, Y.; Hendler, T.
Abstract : Background: Military training is a chronic stressful period that often induces stress-related psychopathology. Stress vulnerability and resilience depend on personality trait anxiety, attentional threat bias and prefrontal–limbic dysfunction. However, how these neurobehavioral elements interact with regard to the development of symptoms following stress remains unclear. Method: Fifty-five healthy combat soldiers undergoing intensive military training completed functional magnetic resonance imaging (fMRI) testing while performing the dot-probe task (DPT) composed of angry (threat) and neutral faces. Participants were then stratified according to their bias tendency to avoidance ( n = 25) or vigilance ( n = 30) groups, categorized as high or low trait anxiety and assessed for post-stress symptom severity. Results: Avoidance compared to vigilance tendency was associated with fewer post-trauma symptoms and increased hippocampal response to threat among high anxious but not low anxious individuals. Importantly, mediation analysis revealed that only among high anxious individuals did hippocampal activity lead to lower levels of symptoms through avoidance bias tendency. However, in the whole group, avoidance bias was modulated by the interplay between the hippocampus and the dorsal anterior cingulate cortex (dACC). Conclusions: Our results provide a neurobehavioral model to explain the resilience to post-trauma symptoms following chronic exposure. The model points to the importance of considering threat bias tendency in addition to personality traits when investigating the brain response and symptoms of trauma. Such a multi-parametric approach that accounts for individual behavioral sensitivities may also improve brain-driven treatments of anxiety, possibly by targeting the interplay between the hippocampus and the dACC.